Pemetaan Kemampuan Digital Pada Usaha Mikro Kecil Menengah (UMKM) di Bidang Usaha Kuliner di Kota Palembang - Amelia, Putri Rizky; Antoni, Darius; Coyanda, John Roni (Jurnal Nasional Ilmu Komputer, 2025)
This study focuses on mapping the digital capabilities of Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector of Palembang City. The main objective of this research is to evaluate the adoption of digital technology by culinary MSMEs and identify the factors influencing the gap between MSMEs that have digitally transformed and those that still use traditional methods. This research employs a descriptive quantitative method with data collected through questionnaires, observations, and literature studies. The findings indicate that digital literacy, technological infrastructure, and government support are key factors for successful digital transformation of MSMEs. Digital platforms such as e-commerce and social media play significant roles in enhancing competitiveness and market access. Strategic recommendations include improving digital literacy, expanding technology access, and optimizing government support. This study is expected to contribute to MSME development in Palembang City and accelerate local economic growth